Let a series be defined as .
Now consider the following statements.
is an integer for .
is odd if and only if is odd.
is even, for positive , if and only if is even
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Consider the relation between a 2 n + 2 and a 2 n .
a 2 n + 2 = a 2 n ( 2 n + 1 ) ! ( 2 n + 2 ) ! = 2 ( n + 1 ) a 2 n = 2 2 ( n + 1 ) n a 2 n − 2
Using the fact that a 0 = 1 , we can conclude that a 2 n = 2 n n ! , which is always an even integer for n > 0 . Thus confirming statement 3.
Similarly, a 2 n + 1 = ( 2 n + 1 ) a 2 n − 1 . Noting that 2 n + 1 is always odd and a 1 = a 0 1 ! = 1 , statement 2 is also confirmed.
Statement 1 is a trivial conclusion, if statements 2 and 3 are true.